2011
DOI: 10.1007/s11104-011-1027-0
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground–belowground interactions as a source of complementarity effects in biodiversity experiments

Abstract: Background The positive relationship between biodiversity and ecosystem functioning (BEF) is due mainly to complementarity between species. Most BEF studies primarily focused on plant interactions; however, plants are embedded in a dense network of multitrophic interactions above and below the ground, which are likely to play a crucial role in BEF relationships. Scope In the present review I point out the relevance of aboveground-belowground interactions as a source of complementarity effects in grassland biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 190 publications
2
155
0
Order By: Relevance
“…The Santana et al [47] study published in 2005 was among the first to show that diversity of primary decomposers was related to ecosystem function, and that there is more complementarity and less redundancy in below-ground ecosystems than previously thought. A subsequent review by Eisenhauer [48], supports the theoretical basis for diversity effects on ecosystem function through complementarity in below-ground systems, whereas Bardgett and van der Putten [49] have argued that species richness only has effects in very simple systems because there is much redundancy. Most recently, analyses of European grasslands by Soliveres et al [50] showed that multitrophic diversity strongly predicted ecosystem functions, and that diversity of microbial decomposers has a particularly strong effect.…”
Section: Latitudinal Gradientsmentioning
confidence: 99%
“…The Santana et al [47] study published in 2005 was among the first to show that diversity of primary decomposers was related to ecosystem function, and that there is more complementarity and less redundancy in below-ground ecosystems than previously thought. A subsequent review by Eisenhauer [48], supports the theoretical basis for diversity effects on ecosystem function through complementarity in below-ground systems, whereas Bardgett and van der Putten [49] have argued that species richness only has effects in very simple systems because there is much redundancy. Most recently, analyses of European grasslands by Soliveres et al [50] showed that multitrophic diversity strongly predicted ecosystem functions, and that diversity of microbial decomposers has a particularly strong effect.…”
Section: Latitudinal Gradientsmentioning
confidence: 99%
“…Cultural management practices, such as multiple-cropping and crop rotations can offer a form of biological disease and pest control (Hao et al 2010). Crops, when grown in combination with other species, show less reduction in productivity and damage due to pest and disease incidence, than when grown as a sole crop (Trenbath 1993;Eisenhauer 2012). …”
Section: Suppression Of Soil-borne Diseases and Pestsmentioning
confidence: 99%
“…Endo-and epi-phytic rhizobacteria, such as Herbaspirillum, but also AM fungi, can benefit a host plant by promoting plant growth via biological N fixation, nutrient solubilisation, synthesis of hormones and vitamins, by biological disease control, and via inducing systemic resistance (Altieri 1995c;Eisenhauer 2012;Monteiro et al 2012). In most cases, biological control results from bacterial production of metabolites, such as antibiotics and hydrogen cyanide, which directly inhibit the pathogen, (Kloepper et al 1999).…”
Section: Plant-growth-promoting Rhizobacteria (Pgpr)mentioning
confidence: 99%
See 2 more Smart Citations